PENYUSUNAN RENCANA PEMULIHAN SEBELUM TERJADI BENCANA (PRE DISASTER RECOVERY PLANNING) SEBAGAI UPAYA MEMITIGASI RISIKO KEMUNGKINAN KEJADIAN BENCANA TANAH LONGSOR DI KABUPATEN PURWOREJO (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2022)
Landslides is a high-risk threat in the Kaligesing district area, Bener district and Bruno district in Purworejo Regency. This refers to RT/RW Regency documents, History of landslides and results of field searches conducted by the service team. This activity aims to compile a plan for recovery before the disaster (Pre Disaster Recovery Planning) will occur a possible landslide in Purworejo Regency. Method of using activities ECLAC (Economic Commission for Latin America and the Caribbean) which is used analyzes analyzes each sector of damage and losses and the method of assessment of damage and losses (Damage and Loss Assessment). This activity was carried out in 5 stages which were completed in a duration of 6 months. The results of the high impact area of ​​landslides occurred in 31 villages with 108 hamlets in the Kaligesing District, Bener District and Bruno District, as well as the potential threat of disaster for a total of 60,515 inhabitants living in the area. Evaluation of damage and loss of impact from the possibility of a landslide in Purworejo Regency worth Rp 417.617.458.000, with the total post-disaster recovery needs worth Rp 207.146.141.000. The Recovery Plan Document Before a Disaster can be legalized by the Purworejo Regency Government as a disaster planning document, action plan for rehabilitation and construction of landslides, and guidelines with legal force in the implementation of rehabilitation and construction of landslide disasters in Purworejo Regency.